Introduccion a la Contabilidad Internacional (Book). - Mills, Patti A.; Brief, Richard P. (The Accounting Review, 1989)
Abstract Reviews the book "Introducción a la Contabilidad Internacional," by Jose Antonio Gonzalo Angulo and Jorge Tua Pereda.